Descriptions of two new genera and six new species of ghost-moths (Lepidoptera: Hepialoidea: Hepialidae) from south-eastern and southern Brazil - Mielke, Carlos G.c.; Grehan, John R.; Koike, Ricardo M. (Zootaxa, 2021)
Agripialus gen. n. and Mutipialus gen. n. are described to accommodate the following species: A. campos sp. n., A. variabilis sp. n., A. itatiaia sp. n., A. caparao sp. n., M. dilatus sp. n., and M. monticolus sp. n. All are from southeastern and southern Brazil. Diagnostic characters suggest a closer phylogenetic relationship between these two genera, than to any other described genus.